Corrosion resistance of concrete strengthened with fibre-reinforced polymer sheets. Issue 2 (27th January 2022) - Tu, Yongming; Liu, Dongyun; Yuan, Lei; Zhang, Yu
Abstract : The corrosion resistance of concrete strengthened with three types of fibre-reinforced polymer (FRP) sheets (unidirectional carbon-FRP (CFRP), unidirectional basalt-FRP (BFRP) and bidirectional BFRP) was evaluated under chloride attack and the combined attack of chloride and ultraviolet radiation. After different corrosion durations, powder samples were collected from various depths of the concrete specimens to measure the total chloride ion concentrations (CICs). Scanning electron microscopy (SEM) was conducted to analyse the microscale morphology changes of the concrete surface layer, FRP fibre layer and resin matrix layer before and after combined attack. The results showed that all three types of FRP sheet provided significant chloride ion resistance, with the barrier effect of CFRP being better than that of BFRP under the same conditions. The total CIC of the FRP-strengthened concretes was higher under the combined attack than under chloride attack alone. The SEM observations showed that the resin matrix and fibre filaments of the FRP layer under combined attack were damaged, resulting in an increase in the permeability of the FRP-strengthened concretes. Finally, a time-varying model of CIC inside the FRP-strengthened concrete under chloride attack was established.